Recombinant Rift Valley fever viruses encoding bluetongue virus (BTV) antigens: Immunity and efficacy studies upon a BTV-4 challenge. - Sandra Moreno; Eva Calvo-Pinilla; Stephanie Devignot; Friedemann Weber; Javier Ortego; Alejandro Brun (Public Library of Science (PLoS), 2020)
Background Many ruminant diseases of viral aetiology can be effectively prevented using appropriate vaccination measures. For diseases such as Rift Valley fever (RVF) the long inter-epizootic periods make routine vaccination programs unfeasible. Coupling RVF prophylaxis with seasonal vaccination programmes by means of multivalent vaccine platforms would help to reduce the risk of new RVF outbreaks. Methodology/principal findings In this work we generated recombinant attenuated Rift Valley fever viruses (RVFVs) encoding in place of the virulence factor NSs either the VP2 capsid protein or a truncated form of the non-structural NS1 protein of bluetongue virus serotype 4 (BTV-4). The recombinant viruses were able to carry and express the heterologous BTV genes upon consecutive passages in cell cultures. In murine models, a single immunization was sufficient to protect mice upon RVFV challenge and to elicit a specific immune response against BTV-4 antigens that was fully protective after a BTV-4 boost. In sheep, a natural host for RVFV and BTV, both vaccines proved immunogenic although conferred only partial protection after a virulent BTV-4 reassortant Morocco strain challenge. Conclusions/significance Though additional optimization will be needed to improve the efficacy data against BTV in sheep, our findings warrant further developments of attenuated RVFV as a dual vaccine platform carrying heterologous immune relevant antigens for ruminant diseases in RVF risk areas.